Deterioration in Renal Function after Beta-blockade in Patients with Chronic Renal Failure and Hypertension. Issue 5912 (27th April 1974) - Warren, David J.; Swainson, C. P.; Wright, N.
Abstract : Treatment of hypertension with beta-blocking agents in three patients with moderately severe chronic renal failure was followed by rapid deterioration of renal function. In two of the patients the need for maintenance haemodialysis was accelerated but renal function in the third reverted to pretreatment levels after the drug was stopped. These findings suggest that until more is known about the effects of beta-blocking drugs they should not be given to patients with moderately severe renal failure.